Pengaruh Exposure Konten YouTube Edukasi Finansial Timothy Ronald terhadap Literasi Keuangan Mahasiswa Universitas 'Aisyiyah Yogyakarta - chikita fauzia ismardi; Herlambang Jati Kusumo; Dias Regian Pinkan (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines the effect of exposure to Timothy Ronald's financial education YouTube content on the financial literacy of students at Universitas 'Aisyiyah Yogyakarta. An explanatory quantitative approach was used with a Likert-scale questionnaire distributed to 76 students from the 2023 cohort (Communication, Accounting, and Psychology programs) selected through purposive sampling. Data were analyzed using simple linear regression with SPSS. Results show media exposure has a positive and significant effect on financial literacy (t = 14.210, sig. < 0.001), with R² = 0.732, meaning 73.2% of the variance in financial literacy is explained by media exposure. The regression equation is Y = 9.880 + 0.587X. Findings are interpreted through Uses and Gratifications Theory, which positions students as active audiences who consume digital financial content to fulfill cognitive needs.